Integrity As A Shield Against Fraud In Activity Management Unit (AMU) Fund Management: Empirical Evidence From Sragen Regency - Heppy Purbasari; Kusuma Wijayanto; Syahrina Noormala Dewi; Rizky Ramadhan Wibisono (CV. Sakura Digital Nusantara, 2026)
Purpose – This study seeks to assess and analysis the impact of competence, internal control systems, and anti-fraud awareness on fraud prevention, while also examining the role of integrity as a moderating variable. Design/methodology/approach – This study employs a quantitative methodology, encompassing a population of 18 AMU in Sragen Regency and a sample of 48 respondents, which includes the chairindividual, secretary, treasurer, verification team, and supervisory board of AMU. This research utilises primary data. The data analysis method employs multiple regression analysis and Moderated Regression Analysis (MRA) utilising the SPSS application. Finding/Results – The internal control system and anti-fraud awareness impact fraud prevention; however, competence does not affect fraud prevention. Integrity has been demonstrated to enhance the impact of anti-fraud awareness on fraud prevention. Nonetheless, integrity cannot mediate the relationship between competency and the internal control system about fraud prevention. These findings suggest that fraud prevention relies not only on technical measures and organisational controls but also on enhancing the integrity and ethical conduct of individualnel within the company. Originality/Value – This research’s originality is in examining integrity as a moderating variable in fraud prevention at AMU, a local community fund management institution.